Neurotoxicity-sparing radiotherapy for brain metastases in breast cancer: a narrative review - Buczek, Dagmara; Zaucha, Renata; Jassem, Jacek (Frontiers in Oncology, 2024)
Up to 10-30% of breast cancer patients will develop metastases to the brain or meninges. Radiotherapy remains one of the main treatments for intracranial metastases. Although radiotherapy prolongs the survival of breast cancer patients, it is associated with considerable toxicity, which is particularly manifested in cognitive function deterioration. Animal studies suggest that these sequelae result mainly from radiation damage to the hippocampus. Avoiding this structure during brain radiotherapy and its pharmacological protection have been the subjects of multiple trials. Another brain-sparing approach that has emerged in the standard management of countable brain metastases is stereotactic radiotherapy. We present current knowledge on the efficacy and safety of these strategies in breast cancer patients with brain metastases.